2016
DOI: 10.1093/ofid/ofw141
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Switch From Nevirapine-Based Antiretroviral Therapy to Single Tablet Rilpivirine/Emtricitabine/Tenofovir Disoproxil Fumarate in Virologically Suppressed Human Immunodeficiency Virus-1-Infected Rwandans

Abstract: There is a need to improve antiretroviral options in Africa. This study shows switching from a neviripine-based treatment to co-formulated rilpivirine/emtricitabine/tenofovir disoproxil fumarate in virologically suppressed Rwandans is safe and non-inferior to continued nevirapine-based therapy at 24 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, the switching strategies were different between that study and our study. The NRTI backbones before switching to TDF/FTC/RPV in the Rwandan study included TDF (63%), azidothymidine (35%), and abacavir (1%) combined with 3TC [11]. In our study, 70% used TDF + 3TC and 30% used TDF/FTC as backbones.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the switching strategies were different between that study and our study. The NRTI backbones before switching to TDF/FTC/RPV in the Rwandan study included TDF (63%), azidothymidine (35%), and abacavir (1%) combined with 3TC [11]. In our study, 70% used TDF + 3TC and 30% used TDF/FTC as backbones.…”
Section: Discussionmentioning
confidence: 99%
“…Other than efficacy, the switch to RPV-based regimens in our study demonstrated a beneficial effect on total cholesterol and triglyceride. The switch trial in Rwanda also showed a trend toward a reduction in total cholesterol and HDL-C in the RPV switch arm compared with the NVP continuation arm, but no significant differences were detected in other fasting lipid measurements at week 24 [11]. A prospective, open-label, controlled trial in the Netherlands showed significant decreases in total cholesterol, HDL-C, and LDL-C over 24 weeks after switching from NVP to RPV [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations